The infection of mycovirus down regulates Aa-milR13 to weaken the pathogenicity of the Alternaria alternata f. sp. mali - Zhang, Jingyi; Li, Chenjiao; You, Shaopeng; Feng, Yuyao; Liu, Mingyi; Li, Bo; Wang, Shutong; Cao, Keqiang; Wang, Yanan (Frontiers in Plant Science, 2025)
This study explored the association between differentially expressed miRNA Aa-milR13 in Alternaria alternata f. sp. mali strains with and without virus infection, and the regulation of fungal host pathogenicity by viruses. MiRNA sequencing was conducted on a hypovirulent strain (QY21) with compound infection of Alternaria alternata chrysovirus 1 (AaCV1) and Alternaria alternata magoulivirus 1 (AaMV1), a hypovirulent strain (QY21-C1) with single AaMV1 infection, and a virus-free strain (QY21-C2). Fourteen miRNAs with significant differential expression were identified. Aa-milR13 was significantly downregulated in virus-infected strains and validated by RT-qPCR. Structural analysis of the Aa-milR13 sequence identified that the mature Aa-milR13 is located at the 5’ end of its precursor stem-loop structure. Knockout of Aa-milR13 in QY21-C2 resulted in slower hyphal growth, darker colony color, and reduced pathogenicity, resembling virus-infected strains. Conversely, overexpression of Aa-milR13 led to accelerated hyphal growth, lighter colony color, and significantly enhanced pathogenicity.Three target genes of Aa-milR13, subtilisin-like protein (AaSLP,cinr CC77DRAFT_1100266), DUF431-domain-containing protein (DUF431, CC77DRAFT_1022347), and high-affinity nitrate transporter NrtB (NrtB, CC77DRAFT_1056077), were predicted and confirmed by RT-qPCR to be negatively correlated with Aa-milR13 expression. Bioinformatics analysis indicated that Aa-milR13 targets the CDS regions of the potential target genes through cleavage, with Watson-Crick pairing of AU, CG, wobble pairing of GU, and various pairing patterns such as AA, AC, AG, GG, UU, UC, etc. This study suggests that fungal virus infection downregulates Aa-milR13, upregulating its targets, potentially contributing to reduced fungal pathogenicity. This is the first report of small RNAs acting as an intermediate bridge in the regulation of fungi virulence by fungal viruses. The research results lay the foundation for elucidating the mechanism of small RNA-involved regulation of fungi hypovirulence by fungal viruses and provide theoretical support for the use of fungal viruses in the control of crop fungal diseases.